EOS® biplanar X-ray imaging: Concept, developments, benefits, and limitations. (February 2016) - Melhem, Elias; Assi, Ayman; El Rachkidi, Rami; Ghanem, Ismat
Abstract: Purpose: In 1992, Georges Charpak invented a new type of X-ray detector, which in turn led to the development of the EOS ® 2D/3D imaging system. This system takes simultaneous anteroposterior and lateral 2D images of the whole body and can be utilized to perform 3D reconstruction based on statistical models. The purpose of this review is to present the state of the art for this EOS ® imaging technique, to report recent developments and advances in the technique, and to stress its benefits while also noting its limitations. Methods: The review was based on a thorough literature search on the subject as well as personal experience gained from many years of using the EOS ® system. Results: While EOS ® imaging could be proposed for many applications, it is most useful in relation to scoliosis and sagittal balance, due to its ability to take simultaneous orthogonal images while the patient is standing, to perform 3D reconstruction, and to determine various relationships among adjacent segments (cervical spine, pelvis, and lower limbs). The technique has also been validated for the study of pelvic and lower-limb deformity and pathology in adult and pediatric populations; in such a study it has the advantage of allowing the measurement of torsional deformity, which classically requires a CT scan. Conclusions: The major advantages of EOS ® are the relatively low dose of radiation (50–80 % less than conventional X-rays) that the patient receives and the possibility of obtaining a 3D reconstruction of the bones. However, this 3D reconstruction is not created automatically; a well-trained operator is required to generate it. The EOS ® imaging technique has proven itself to be a very useful research and diagnostic tool.